Dominant Factors in Complementary Food Feeding in Babies and Toddlers - Octaviana, Amrina; Roslina, Roslina; Trianingsih, Indah; Marlina, Marlina; Indrasari, Nelly (Poltekkes Kemenkes Tanjung Karang, 2023)
52.8% of all Indonesian children, or those between the ages of 6 and 23 months, do not obtain the nourishment they require throughout the first two years of life in order to grow and develop as they should. One of Lampung province's areas, Tulang Bawang Regency, has the highest rate of children under five who are very thin (BB/TB), at 7.7%. The purpose of the research was to determine the important element in supplemental feeding of babies and toddlers in Tulang Bawang Regency in 2021. Analytic correlation using a cross-sectional design characterized this sort of study. A sample of 132 women who have children between the ages of 6 and 24 months was acquired by sampling utilizing stratified random sampling. Chi Square analysis in bivariate form and Logistics Regression Analysis in multivariate form. According to statistical analyses, complementary feeding behavior is significantly influenced by a number of internal and external factors, including type of food, frequency of feeding, amount of feeding, and community culture, as well as internal factors like age of knowledge of food, child's activities, and child's health history. Babies and toddlers at the Banjar Baru Community Health Center in the Tulang Bawang Regency in 2021 (p = 0.05). Based on the OR values of these factors, Child Health (OR=8,449) is the most important factor in providing complementary feeding to babies and toddlers in the Banjar Baru Health Center region of the Tulang Bawang Regency in 2021. For families with young children, there is a need for socialization over how to feed newborns and toddlers complementary feeding that are healthy and appropriate, as well as to revive the role of the posyandu in neighborhood events.